Effects of Long-Term Treatment with Atorvastatin and Rosuaastatin on Active Avoidance Test in Intact Rats - Maria Georgieva-Kotetarova; Ivanka Kostadinova; Delian Delev (Journal of Biomedical & Clinical Research)
Statins are widely used for treatment of hyperlipidemia. They have been shown to possess pleiotropic effects apart from their lipid-lowering activity - anti-inflammatory, immunomodulatory, and neuroprotective. Most studies suggest that statins can protect the brain against damage but it is not clear whether they improve cognitive function in patients without neuropathy. The aim of the present study was to investigate the effect of 3-month treatment with atorvastatin and rosuvastatin on learning and memory processes in rats without brain damage. Wistar rats were treated orally for 90 days with atorvastatin and rosuvastatin at a dose of 10 mg/kg b. w. in parallel with the vehicle-treated group. After that period, learning ability and memory retention was evaluated using an active avoidance test - automatic reflex conditioner (shuttle box). The learning session was carried out on 5 consecutive days. Memory retention test was performed on day 12. The following behavioral reactions were investigated: conditioned responses (avoidance), unconditioned responses (escapes), and intertrial crossings. We found increased number of conditioned responses in groups, treated with atorvastatin 10 mg/kg b.w., and with rosuvastatin 10 mg/kg b.w. during the learning session and on the memory retention test, as compared to the same-day control group. The atorvastatin-treated group showed an increased number of unconditioned responses on days 1 and 2, as compared to the control group. In the group treated with Rosuvastatin there was an increased number of escapes on days 1,2 and 4, as compared to the vehicle-treated group. Atorvastatin and rosuvastatin at a dose of 10 mg/kg b.w. improved processes of learning and memory retention after the 3-month treatment.